IMPLEMENTASI PENGGUNAAN MEDIA GAMBAR BUKU BRAINY DALAM PEMBELAJARAN KETERAMPILAN MEMBACA PERMULAAN KELAS 2 SD N 1 PEGANJARAN - Dwi Arum Syafitri (STKIP Subang, 2022)
ABSTRACT The background that drives this research is the difficulty in learning to read beginning. This can happen because during COVID-19 the learning process is carried out with the BDR (Learning From Home) or PJJ (Distance Learning) system, children lack reading practice. The problem in this research is how is the learning process carried out by the teacher using the Brainy book picture media for reading skills at the beginning of grade 2 SD N 1 Peganjaran? The purpose of the study was to describe the learning process using the image media of the Brainy book for reading skills at the beginning of grade 2 SD N 1 Peganjaran. This type of research is qualitative in the form of descriptive. Methods of data collection using the results of observations, interviews and documentation. The research population is grade 2 SD N 1 Peganjaran. The data analysis method used is data collection, data reduction, data review, and conclusion drawing, as well as verification. Based on the results of this study, it shows that the Brainy book picture media makes the learning process fun and makes students more active in the learning process with the media accompanied by many games. Brainy book picture media makes it easy for students to understand letters in words, makes students interested in learning, and increases student scores. The conclusion of this research is the learning process carried out by the teacher using the Brainy book picture media, namely the teacher using the student centered method (Student Centered Learning) so that students are active in learning and it is easier to understand words or sentences in the Brainy book picture media. For the duration in the learning process used by the teacher using the Brainy book picture media, which is about 30 minutes. Keywords: Reading Difficulties, Learning Media, Brainy Books